2014
DOI: 10.1186/s12989-014-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of microbial and chemical composition in toxicological properties of indoor and outdoor air particulate matter

Abstract: BackgroundAmbient air particulate matter (PM) is increasingly considered to be a causal factor evoking severe adverse health effects. People spend the majority of their time indoors, which should be taken into account especially in future risk assessments, when the role of outdoor air particles transported into indoor air is considered. Therefore, there is an urgent need for characterization of possible sources seasonally for harmful health outcomes both indoors and outdoors.MethodsIn this study, we collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Recently, studies have begun to focus on how these dust exposures can impact human health (Happo et al, 2008(Happo et al, , 2014Hogervorst et al, 2007;Jalava et al, 2009). These studies have indicated that certain toxic compounds, both indoors and outdoors, have steadily been accumulating over time (Garrison et al, 2014;Ravindra et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, studies have begun to focus on how these dust exposures can impact human health (Happo et al, 2008(Happo et al, , 2014Hogervorst et al, 2007;Jalava et al, 2009). These studies have indicated that certain toxic compounds, both indoors and outdoors, have steadily been accumulating over time (Garrison et al, 2014;Ravindra et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Outdoor contaminants (including microbes) typically affected indoor air quality most during the summer months and less during the winter time. Conversely, both indoor contaminants as well as microbes emanated from indoor sources during the winter months (Happo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent study conducted in a small Finnish town, Kuopio, the particulate sources, compositions and the induced toxicological responses showed considerable seasonal variations (Happo et al, 2014). From the particle sources, engine emissions and other combustion sources have been associated with mortality (Clancy et al, 2002;Hoek et al, 2002), exacerbations of heart disease (Lanki et al, 2006) and increased cardiovascular emergency room visits (Metzger et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Particulate matter indoors may contain a different range of chemicals from that encountered outside, 25 including those from air fresheners 26 and microbial products. 27 In addition, polyaromatic hydrocarbons are emitted in large amounts during cooking and frying, 28 all made worse by the sealing of buildings for energy conservation. Indoor air is enriched in biological pollutants such as allergens from dust mites, pets and fungi, as well as microorganisms that become concentrated especially in damp conditions.…”
Section: Quantify the Relationship Between Indoor Air Pollution And Hmentioning
confidence: 99%